THE EFFECT OF RHEUMATIC GYMNASTICS AND COLD WATER THERAPY ON THE REDUCTION OF PAIN SCALE IN THE ELDERLY WITH GOUT ATHRITIS WORK AREAMUARA BANGKAHULU HEALTH CENTER CITY OF BENGKULU - Rona Uli Arta Siahaan; Sariman Pardosi; Efrizon Hariadi (Poltekkes Kemenkes Banten, 2026)
Elderly is a person who has reached the age of ≤60 years which is a stage that every individual goes through in the life process. Gout Athritis disease, also known as gout, is a type of arthritis characterized by hyperuricemia or high levels of uric acid in the blood causing symptoms of pain in various joints. World Health Organization (WHO) data reported that the number of people with gout arthritis in the world reaches 335 million people and this number continues to increase every year. One of the non- pharmacological therapies for pain that can be done is Rheumatic Gymnastics and Cold Water Therapy. This study is to determine the effect of rheumatic gymnastics and Cold Water Therapy on reducing the pain scale in the elderly with Gout Athritis in the working area of the Muara Bangkahulu Health Center, Bengkulu City in 2025. This type of research is a quasi experiment with a pre- post with control group with a total sample of 52 respondents. The intervention of rheumatic gymnastics and Cold Water Therapy was carried out 3 times for 2 weeks with the instrument used being the Numeric Rating Scale. Statistical tests using Mann-whitney showed a p-value of 0.034 (p value α 0.05) so it can be interpreted that there is an effect ≤ of rheumatic gymnastics and Cold Water Therapy on the reduction of pain scale in the elderly with Gout Athritis in the working area of the Muara Bangkahulu Health Center.